España en América : las tropas peninsulares en el sistema defensivo indiano durante el siglo XVIII (2016)
ABSTRACT: This article is a research of contribution of Spanish peninsular tropos to the defense of Indias in eighteen century. The Spanish defensive system had deep military reforms that affected the role of American troops and forced the authorities in Madrid to move an increasing number of units of the península to reinforce the defenses. It is argued that these units were essential to the success of the Spanish military presence at the end of the century.